An investigation to develop student feedback literacy skills in the dental science UG curriculum - Davis, Siobhan (My University, 2023)
Educators in the clinical learning environment should provide more than didactic supervision of practice and performance scoring. Appropriate feedback in this context is critical to the development of student competence and confidence1. Numerous calls made for healthcare (HC) students to be supported to increase their agency and active engagement with the feedback process, that is, to intentionally support their feedback literacy skills. We have developed an evidence-based, online multimedia resource designed to facilitate the development of feedback skills for HC undergraduate students. Discussion: Principles of good feedback literacy skills support students in being active agents in the feedback process. There is scope in acknowledging that students should be active participants in the process of feedback and the importance of student knowledge regarding pedagogy around feedback, especially, in relation to the dental clinical learning environment, which is a unique learning environment.
ADEE Annual Meeting 2023
Keywords: Dental education; Dentistry; Technology Enhanced Learning